2021
DOI: 10.1093/ckj/sfab135
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hypertension in kidney transplantation by ambulatory blood pressure monitoring: a systematic review and meta-analysis

Abstract: Background Hypertension (HTN) is common following renal transplantation and it is associated with adverse effects on cardiovascular (CV) and graft health. Ambulatory blood pressure monitoring (ABPM) is the preferred method to characterize blood pressure (BP) status, since HTN misclassification by office BP (OBP) is quite common in this population. We performed a systematic review and meta-analysis aimed at determining the clinical utility of 24h ABPM and its potential implications for the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 111 publications
1
16
0
1
Order By: Relevance
“…In addition, we observed an overall beneficial effect of KTx on BP control; the proportion of KTRs with concordant lack of control by both office and ABPM was reduced, whereas the percentage of patients with concordant control of BP was almost quadrupled. Despite these beneficial effects, the rates of uncontrolled hypertension in our cohort are considered high and are similar to those reported in recent meta-analyses [ 30 ]. In addition, no significant changes were noted in dipping patterns, with the proportion of non-dippers and reverse dippers remaining considerably high (53.1% and 31.3%, respectively), similar to previously reported rates (42% and 34%) 12 months after KTx [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, we observed an overall beneficial effect of KTx on BP control; the proportion of KTRs with concordant lack of control by both office and ABPM was reduced, whereas the percentage of patients with concordant control of BP was almost quadrupled. Despite these beneficial effects, the rates of uncontrolled hypertension in our cohort are considered high and are similar to those reported in recent meta-analyses [ 30 ]. In addition, no significant changes were noted in dipping patterns, with the proportion of non-dippers and reverse dippers remaining considerably high (53.1% and 31.3%, respectively), similar to previously reported rates (42% and 34%) 12 months after KTx [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, office BP has several limitations in the diagnosis and management of hypertension compared with the gold standard of BP measurement, which is 24-h ABPM [ 12 , 13 ]. The latter enables identification of white coat and masked hypertension phenotypes, which are particularly common in KTRs [ 30 ], and displays stronger associations than office BP with target-organ damage [ 11 ]. Ιn view of the above, recent guidelines and consensus documents highlight the need of more extended ABPM use in the diagnosis and management of hypertension in KTRs [ 5 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations have shown that the rhythm disorder after renal transplant remained, such as sleep disturbance, fatigue, hypertension and metabolic impairment in ERSF patients, which indicates that circadian clock system involved in the graft's function of renal transplant patient (Mendoza-Romo-Ramírez, et al, 2021) (Pisano, et al, 2021). The literature has demonstrated that nocturnal surgery might increase the morbidity and mortality with a higher risk of postoperative complications compared to daytime surgery in lung transplant and cardiac surgery and myocardial tolerance to IRI imposed daytime variation (Qiu, et al, 2018) (Montaigne, et al, 2018) (Cunningham, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, patients with ERSF show a variety of rhythm disorders of physiological functions, such as low sleep quality, recurrence of hypertension, restless legs syndrome and so on, which can be aggravated by hemodialysis treatment (So, et al, 2020) (Firsov, et al, 2018). Unfortunately, renal transplantation can only temporarily improve a series of symptoms caused by circadian rhythm disorder, but the long-term syndromes still exist (Mendoza-Romo-Ramírez, et al, 2021) (Pisano, et al, 2021). Meanwhile, the latest cohort study with 10291 patients observed that compared to nocturnal de-clamping, day-time de-clamping was associated with a better prognosis of kidney transplantation despite a longer duration of cold ischemia (Montaigne, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent systematic review confirmed that altered circadian BP profile and nocturnal hypertension are frequent in the transplant population [15]. Moreover, the use of ABPM in kidney transplant recipients indicated a great proportion of both masked hypertension and white-coat hypertension [15].…”
Section: Blood Pressure Measurementmentioning
confidence: 97%